Collaborative Innovation for Green Economy Implementation: A Case Study in Sumedang Regency - Anne Friday Safaria; Dhesti Widya Nurhasanah Ningrum; Rika Kusdinar (Department of Public Administration, 2026)
This study examines the application of collaborative innovation in the implementation of a green economy in Sumedang Regency, as a sustainable development approach that combines economic prosperity with environmental conservation. The background of this study is the challenges faced by local governments in integrating green economy principles, including cross-sectoral coordination, limited resources, and low public awareness. Collaborative innovation is seen as a potential strategy to overcome these obstacles, by involving the active participation of the government, the private sectors, academia, and communities in designing and implementing sustainability-based programs. The method used was a qualitative case study. Data were collected through literature review, focus group discussions, and field studies that included observation, interviews, and documentation. Data analysis was conducted using the iterative model of Miles and Huberman. The results indicate that collaborative innovation in Sumedang Regency is developing in various sectors, such as waste management, organic farming, environmental conservation, and renewable energy. Various innovative green economy collaborations have been implemented, including the Reduce, Reuse, Recycle (TPS 3R) Waste Processing Facility, the Waste Bank Unit, the RDF (Refuse-Derived Fuel) processing partnership, maggot processing, the development of microbial-based organic fertilizer QRR (Quantum Rotan Revo), and the Climate Village Program. Policy support, the government's role as a facilitator, multi-stakeholder involvement, and synergy between public and private actors are key driving factors. However, technical, managerial, and financing challenges still limit program optimization. Collaborative innovation has great potential to strengthen the implementation of a green economy in Sumedang. Success can be achieved by expanding the scale of implementation, integrating cross-sector programs, enhancing the government's role as a facilitator, intermediary/liaison in collaboration, improving human resource capacity, and establishing a clear regulatory framework. Thus, this research is expected to contribute to the theory and practice of public administration, especially for the role of government as a policy maker and implementer.